Reverse Transcriptase PCR detection of Hepatitis A virus (HAV) in cultured and wild shellfish from the Peninsular of Malaysia - Md. Nordin, Wan Norhana; A. Rahim, Masazurah; Mahyudin, Nor Ainy; I., Ismail (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Hepatitis A is a liver infection caused by the hepatitis A virus (HAV). Outbreaks of hepatitis A have been linked to the consumption of both raw and cooked shellfish. These outbreaks could induce a public confidence problem over shellfish safety and may result in important economic losses for the seafood industry. The work presented in this study investigated the presence of HAV in shellfish from Peninsular Malaysia. A total of 365 of cultured and wild shellfish from 36 sampling locations located throughout Peninsular Malaysia were examined using a commercial nucleic acid extraction and reverse transcription -polymerase chain reaction (RT-PCR) kit. HAV was not detected in almost all of the shellfish samples examined. Only one cockle sample from Changkat, Seberang Perai was positive for HAV. The results suggest the absence of HAV or very low amount of HAV viral particles in most of the shellfish examined.